CONDUCTIVITY OF SODIUM HALIDES IN BINARY MIXTURES OF ETHYLENE AND PROPYLENE GLYCOL WITH WATER - Cookey, Grace Agbizu; Osi, Valentine; Umah, Favour Chidera (Department of Chemistry Faculty of Science and Technology UIN Walisongo, 2025)
The conductivity behavior of sodium halides (NaBr and NaCl) in binary solvent mixtures of water with ethylene glycol (EG) and propylene glycol (PG) is crucial for optimizing electrolyte formulations in industrial applications. This study investigated the effects of varying glycol mole fractions (0 to 0.9) and salt concentrations (0.01 g to 0.13 g) on specific conductivity. The measurements were performed using a calibrated conductivity meter at room temperature (30 ± 2°C). The results revealed distinct patterns affected by solvent composition and salt type. In PG-water mixtures, specific conductivity increased with higher PG content; NaBr values rose from 1.02 μS/cm at a 0 mole fraction to 5.78 μS/cm at a 0.9 mole fraction for 0.01 g of NaBr. NaCl showed a similar but less pronounced trend, ranging from 0.4 μS/cm to 2.02 μS/cm under comparable conditions. Conversely, EG-water mixtures exhibited decreasing conductivity with increasing EG content, as NaBr values declined from 7.45 μS/cm at 0 mole fraction to 0.67 μS/cm at 0.9 mole fraction. These higher conductivity values of NaBr were attributed to its larger ionic radius and greater ionic mobility. These findings shed lights on ion–solvent interactions in mixed-solvent systems and have potential applications in electrolytic processes, energy storage, and industrial formulations requiring precise conductivity control.